A aurora de uma clínica sob os anúncios de sua crise: uma arqueogenalogia do espaço clínico psicológico no Brasil - Lima Neto, Valdir Barbosa (2019)
This work aims at analyzing the constitution of the professional and academic practices of the national psychological clinic, emerging under the announcements of its crisis. Taking the discourses that compose a mosaic of narratives about the emergence of the psychological clinic in Brazil in the early 1960s and the statements of its crisis from the late 1970s to the present day, was follow the increasing attacks on the constitution of clínical practices in psychology. Curiously, along with such discourses, this was perceive the strengthening of "social" as an expanded space of practices in psychology, converging to new discursive formations that affirm the necessity of the expansion and transformation of contemporary psychology. Most of them are situated in the debate about the formation of the psychologist, this was perceive that most of the discourses that deal with the crisis of the psychological clinic trigger a narrative that preaches the need to construct a new conception of subjectivity for the updating and expansion of the formation and performance of the psychologist. In this sense, we will undertake an archeogenealogical investigation on the discourses that criticize and attack the psychological clinic in order to catch the emergence of such subject-form in the curricular space of psychologists, in the midst of their professional practice. This work will be organize in three moments, where will first address a story about the so-called crisis of clínical psychology in Brazil, analyzing the narratives triggered in the design of such a crisis. Next, we'll spell out our research tools, with the goal of tuning our pace with the reader, and clarifying points in our research approach. Finally, it will be undertake an analysis of the histórical formation of higher education of psychology in the country, along with the professional movement of the psychologist, accompanying the discursive practices that begin to announce the crisis in Brazilian psychology and yet explain the solution within vocational training. At that moment, It will be relate the emergent events in the history of the formative and curricular narratives of Brazilian psychology, with pedagogical projects, in order to perspective the new form of subjectivity that presents itself in the formations of the current Brazilian psychology. Perspecting that as a new challenge for the contemporary psychologist, the discourse on the crisis of the psychological clinic seems to become a tangle of new contours for science and for the profession of Brazilian psychologists, under the horizon of epistemological, ethical, technical debates and methodological questions about the constitution of a new subject-form for psychology, with a view to effecting a new form-form-profession which whisper and effect with exquisite discretion the strengthening of clínical, expanded under all horizons of psychological action.